Gait impairment associated with neuroimaging biomarkers in Alzheimer’s disease - Kim, Sung-Woo; Kim, Dong Ho; Hong, Jin Yong; Mun, Kyung-Ryoul; Jung, Dawoon; Hong, Ickpyo; Mc Ardle, Riona; Seong, Joon-Kyung; Baek, Min Seok (Nature Publishing Group, 2025)
Research links gait impairment in Alzheimer’s disease (AD) to cognitive abnormalities, brain atrophy, or amyloid-β (Aβ) deposition, with the exact cause unclear. This study investigated the relationship between gait, neuroimaging biomarkers, and cognition across the AD spectrum. We recruited 48 AD dementia patients, 27 with prodromal AD, and 41 cognitively unimpaired individuals, analyzing associations among gait parameters, cognitive scores, Aβ deposition, and cortical atrophy. Path and receiver operating characteristic (ROC) analyses evaluated gait impairment’s interdependent interactions and diagnostic potential. Prodromal AD and AD dementia patients showed significantly slower gait pace than CU (p = 0.014 [velocity], p = 0.003 [step length]), linked to attention and executive functions, widespread Aβ deposition, and cortical atrophy, in the inferior parietal lobule, middle temporal gyrus, precuneus, and insula. Compared to CU, AD dementia patients exhibited greater gait variability and phase (p = 0.017 [step length standard deviation], p = 0.001 [double support percentage]), significantly correlated with cognition and Aβ deposition. Path analysis revealed a combined influence of Aβ deposition, cognitive impairment, and cortical atrophy on gait impairment, with > 80% observed gait impairments directly affected by Aβ deposition. ROC curves for diagnosing AD stages showed significant areas under the curve, suggesting gait characteristics as noninvasive biomarkers for early AD diagnosis and progression monitoring.